Effect of organizational climate upon the job performance of instructors' physical education - M.S. Luqman; J.U. Rehman; Z.U. Islam; S.D. Khan (IP Iermakov S.S., 2020)
Propose: The current study was conducted to examine the effect of organizational climate on the Job Performance of Instructors' Physical Education. Material: A quantitative method was employed for this purpose; a survey research design was used. There was 169 Instructors' Physical Education preferred through stratified sampling technique. A structured questionnaire was administered to collect the data. The data was analyzed using inferential statistics (linear and multiple regression). Results: The results of the study indicated that organizational climate affect job satisfaction significantly. All the dimensions of organizational climate contribute to increasing the Instructors' Physical Education performance. Conclusion: The current study concluded that Instructors' Physical Education not only feel comfortable in a healthy organizational climate but also increase their level of performance. The study also depicted that effective communication structure, reward system, teamwork, career development, and effective planning and decision making strategies are the valuable ingredients to enhance the performance of Instructors' Physical Education. Recommendation: Keeping in view the results of the current study, it is recommended that head of the institution may focus or promote supportive culture in their respective educational institutions to enhance the performance of instructors' physical education.